KARAKTERISASI MORFOLOGI SEL REKOMBINAN DAN PIGMEN HASIL FUSI PROTOPLAS INTERSPESIFIK Phaffia rhodozyma DAN Chlorella pyrenoidosaH Chick - Indah Sulistyarini; Hermin Pancasakti Kusumaningrum; Endang Kusdiyantini (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Protoplast fusion technique is a process offusion between protoplasts of theorganism to other organisms, so that the resulting recombinant cells with varying character derived from its parent. This study did Phaffia rhodozyma interspesies fusion and Chlorella pyrenoidosa. The purpose of this study was to analyze the morphological characteristics of cells results protoplast fusion recombinant yeast P. rhodozyma and microalgae C. pyrenoidosa. Protoplast fusion technique performed in 4 phases, namely the isolation of protoplasts, protoplast fusion, and analysis of recombinant cell morphological characters. The results showed that the recombinant cells have morphological characters derived from the parent P. rhodozyma and of the parent C. pyrenoidosa. But was character of the parent P. rhodozyma more dominant. Recombinant cells capable of producing pigment and lutein astaksanthin. Astaksanthin pigment levels in recombinant cell height in a shorter time than the parent P. rodozyma.